SIMULATION CONTROL OF FLOW IN RATE AND LEVEL OF FLUID IN MINI PLANT BOILER BDT 921 USING PI CONTROLLER WITH FEEDBACK, CASCADE, AND FEEDFORWARD-FEEDBACK CONTROL STRATEGIES - Ramli, Ferisyal
BDT921 mini plant boiler is one of the training facilities related to instrumentation and control with two main processes, namely controlling the boiler tank and heat exchanger. Currently, all controls can be changed using an HMI connected to the PLC. One of the developments that can be done to the BDT921 mini boiler plant is that the training process is not directly applied to the real plant, but by simulation in software. This final project aims to model and create a controller for the subprocess flow rate to the boiler tank and fluid level in the boiler tank. The controller used was a PI controller using the root locus method. The controller is combined with various control strategies that can be applied in a real mini plant, namely feedback, cascade, and feed-forward-feedback. Furthermore, experiments and analyzes of the best control strategy are carried out for the various conditions required. Experiment variations that were carried out were the change in the set point and the addition of the outflow disturbance for controlling the fluid level in the boiler tank of 0.2, 0.4, and 1 m3/h. The PI control parameter obtained for the fluid flow rate are ? K?_pf=0.553 and K_if=0.138, control fluid level with feedback control strategy K_plf=1.852 and K_ilf=0.009, cascade ? K?_plc=21.258 and K_ilc=0.043, and gain feedforward K_ff=0.1. Based on the experimental results, the cascade control strategy produces a good response for small disturbances below 0.4 m3 / h and a good feed-forward-feedback control strategy for disturbances greater than 0.4 m3 / h.